Clinicopathological and prognostic significance of epithelial cell transforming sequence 2 expression in cancers: a systematic review and meta-analysis - Bin Li; Jun-Ping Lin; Zheng Li; Ci Yin; Jian-Bao Yang; Yu-Qi Meng (Artificial Cells, Nanomedicine, and Biotechnology)
Numerous studies have investigated the prognostic significance of ECT2 (epithelial cell transforming sequence 2) expression in patients with cancer. Nevertheless, conflicting results have been obtained. We thus performed a meta-analysis to systematically assess the prognostic significance of ECT2 in cancer. Electronic databases (PubMed and EMBASE) were searched for eligible studies. Hazard ratios (HR) and odds ratios (OR) with 95% confidence intervals (CIs) were used to estimate effect sizes. A total of 5,305 patients from 19 articles and 21 studies were included. The pooled results revealed that high ECT2 expression was correlated with advanced TNM stage (OR = 2.17; 95% CI: 1.42–3.32), positive lymph node metastasis (OR = 2.98; 95% CI: 2.28–3.89), distant metastasis (OR = 2.25; 95% CI: 1.03–4.92), and poor tumour differentiation (OR = 2.25; 95% CI: 1.03–4.92). More importantly, high ECT2 expression was significantly associated with poor overall survival (HR = 2.26; 95% CI, 1.84–2.78) and recurrence-free survival (HR = 1.52; 95% CI, 1.24–1.86). Our results suggested that ECT2 is a promising prognostic indicator and therapeutic target for cancer.